Design of Adaptive Synergetic Controller for One Degree of Freedom Robotic ARM Under External Disturbance - Hamoudi, Ahmed Khalaf; Husain, Suha S. (Universitas Muhammadiyah Yogyakarta, 2025)
In order to manage a one-link robot arm, this research proposes a unique control architecture based on the Synergetic Control (SC) principle. The synergetic control design is initially developed using known system parameters and subjected to external disturbances. However, in practical robotic systems, uncertainties are inherent in the system parameters. As a result, an algorithm known as Adaptive Synergetic Control (ASC) is presented and developed for a robot arm that encounters parameters uncertainty. To estimate disturbances and guarantee the asymptotic stability of the monitored system, adaptive synergetic laws are developed. The adaptive laws and control of the ASC were established to ensure the stability of the controlled robotic arm. The recommended controller addresses the tracking problem of a single-degree-of-freedom (SDOF) robot arm, and disturbance control scenario was conducted and simulated. Additionally, the paper compares the ASC method with the adaptive backstepping control technique to evaluate the effectiveness of ASC, this comparison demonstrated the efficiency of the recommended strategy in terms of maximum tracking error and maximum control effort. The performance of both SC, ASC is demonstrated through computer simulations, showing that the adaptive controller can handle uncertainties as well as disturbance and maintain system stability.